2010
DOI: 10.3146/ps08-015.1
|View full text |Cite
|
Sign up to set email alerts
|

Managing early leaf spot and stem rot with reduced fungicide inputs on disease-resistant peanut cultivars

Abstract: Fungicide inputs are a costly but critical component of peanut production systems in the southeast U.S. Current strategies for reducing fungicide application numbers that are needed to control diseases on peanut include extending application intervals beyond a 2-wk schedule or implementation of a fungicide advisory, such as AU-Pnuts. In this study, fungicide programs with azoxystrobin, chlorothalonil, and tebuconazole, using different application schedules, were compared for the control of early leaf spot and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…The application of sterol biosynthesis inhibitors (SBI) also referred to as DMIs and quinone out side inhibitor (QoI) fungicides are now known to be more effective than previously recommended fungicides such as quintozene and carboxin for the control of SSR (Johnson and Subramanyam 2000, Besler et al 2006, Grichar et al 2010, Augusto and Brenneman 2011. The SBI tri azole systemic fungicides, namely, diniconazole, propiconazole, tebuconazole (Minton et al 1990, Culbreath et al 1992, Adiver and Anahosur 1995, cyproconazole (Culbreath et al 1992, Adiver andAnahosur 1995), hexaconazole (Johnson et al 2007b), difenoconazole (Cilliers et al 2003), and prothioconazole (Augusto and Brenneman 2012), and the QoI strobilurin fungicides, that is, azoxystrobin (Johnson and Subramanyam 2000, Rideout et al 2002, Sconyears et al 2007, Hagan et al 2010) and pyraclostrobin (Hagan et al 2007, Grichar et al 2010, have been proved to give very efficient and effective control of SSR of peanuts. The QoI fungicides should be applied preventively or as early as possible in the disease cycle as these are effective in inhibiting early mycelial growth.…”
Section: Chemical Controlmentioning
confidence: 99%
“…The application of sterol biosynthesis inhibitors (SBI) also referred to as DMIs and quinone out side inhibitor (QoI) fungicides are now known to be more effective than previously recommended fungicides such as quintozene and carboxin for the control of SSR (Johnson and Subramanyam 2000, Besler et al 2006, Grichar et al 2010, Augusto and Brenneman 2011. The SBI tri azole systemic fungicides, namely, diniconazole, propiconazole, tebuconazole (Minton et al 1990, Culbreath et al 1992, Adiver and Anahosur 1995, cyproconazole (Culbreath et al 1992, Adiver andAnahosur 1995), hexaconazole (Johnson et al 2007b), difenoconazole (Cilliers et al 2003), and prothioconazole (Augusto and Brenneman 2012), and the QoI strobilurin fungicides, that is, azoxystrobin (Johnson and Subramanyam 2000, Rideout et al 2002, Sconyears et al 2007, Hagan et al 2010) and pyraclostrobin (Hagan et al 2007, Grichar et al 2010, have been proved to give very efficient and effective control of SSR of peanuts. The QoI fungicides should be applied preventively or as early as possible in the disease cycle as these are effective in inhibiting early mycelial growth.…”
Section: Chemical Controlmentioning
confidence: 99%
“…Though host-plant resistance is the most economically viable option to control this disease, unfortunately, all improved varieties in cultivation today are more or less susceptible to stem rot. Presently, stem rot is managed using chemical fungicides such as azoxystrobin, chlorothalonil, tebuconazole, carbendazim and mancozeb (Hagan et al 1991(Hagan et al , 2010, but their high cost keeps them from being a viable approach, especially for resource-poor smallholder farmers and where productivity is low (1.0-1.5 t/ha), especially in Asia and sub-Saharan Africa. On the other hand, sustainable and ecologically safe methods to manage soilborne pathogens are gaining popularity as concerns on the harmful effects of chemicals increase.…”
Section: Introductionmentioning
confidence: 99%
“…The PEDC (per cent efficacy over disease control) was also very high in T 3 in comparison to other treatments. Hagan et al, (2010) also reported azoxystrobin, chlorothalonil, and tebuconazole, for the control of ELS and stem rot and found the incidence of these diseases were lower with the application of azoxystrobin than chlorothalonil in the 2 out of 3 year"s programs. The azoxystrobin program significantly increased yield compared with the chlorothalonil or tebuconazole.…”
Section: The Following Treatments (Fungicides) Were Used As Seed Dresmentioning
confidence: 99%